CRYPTIC CANVASSES: EMILY CARROLL’S SPATIALIZATION OF HORROR IN WEBCOMICS - Sy, Jose Monfred C. (Journal of English Studies and Comparative Literature; Vol 17 (2018), 2019)
Over the years, comics has been undergoing major transitions given the affordances of evolving technologies and the growing consumer market of born-digital art productions. This paper argues that digitization augments the meaning-making operations and narrative machines of what creators, readers, and scholars categorize as webcomics . The primary task of this commentary is to consider webcomics’ potential to enhance narratives traditionally enjoyed in print or film, particularly of the genre of horror. Unlike other genres such as science fiction or romance, horror is palpable to consumers as an affect. Horror webcomics utilize digitally-enhanced spatial layouts in order to visually articulate this. In demonstrating how digital operations enhance the delivery of horror narratives, this paper focuses on the works of independent comic artist and illustrator Emily Carroll. Her works, especially His Face All Red , evidence how webcomics can be effective platforms for spatializing horror narratives. By employing the infinite canvas and other digital affordances as storytelling techniques, Carroll heightens readers’ unwillingness to have a face-to-face confrontation with the abject —the unnamed non-object—or in these stories’ case, the supernatural monster. This crossover between the grisly genre and the graphic medium makes readers aware that, by virtue of our confrontation with the abject, we ourselves become specters haunting the text. 122 Journal of English Studies and Comparative Literature volume 17 If a fear cannot be articulated, it can’t be conquered. Stephen King, ‘Salem’s Lot